Ramie spraying seedling raising method and device - ZHOU JING; JIN CHENZHONG; MENG GUIYUAN; LI MENGYANG; KANG LINFENG; TANG TING (2016)
The invention discloses a ramie spraying seedling raising method. The method includes the steps: firstly, preparing ramie cuttings; secondly, disinfecting a seedling raising greenhouse, disinfecting bases of the cuttings, fixing the disinfected cuttings in seedling raising tray holes with sponge, and keeping proper temperature and humidity; thirdly, evenly spraying clear water on the bases of the cuttings uninterruptedly with an atomizing device for 4-5 days, and maintaining sufficient sunlight; fourthly, adding plant nutrient solution into the clear water to prepare nutritive water, and spraying the nutritive water to the bases of the cuttings evenly and uninterruptedly with the atomizing device for 3-8 days, maintaining sufficient sunlight till the young seedlings are as high as 15-20 centimeters, and transplanting the seedlings into cultivation field. The invention further discloses a ramie spraying seedling raising device. The method and the device have the advantages of less influence from external envir